Analysis of Service Quality and Brand Image on Customer Satisfaction and Loyalty: Case Study of Precious Metal Products - Abriyanto, Rosnandar; Zulkarnain, Z.; Garnasih, Raden Lestari (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
Abd-el-salam, E. M., Shawky, A. Y., & El-nahas, T. (2013). The impact of corporate image and reputation on service quality, customer satisfaction, and customer loyalty : testing the mediating role. Case analysis in an international service company. 8(1), 130–153. Ahmed, Z., Rizwan, M., Ahmad, M., & Haq, M. (2014). Effect of brand trust and customer satisfaction on brand loyalty in Bahawalpur. Journal of Sociological Research, 5(1), 306–326. https://doi.org/10.5296/jsr.v5i1.6568 Alwie, A. F. (2024). Analysis of Customer Satisfaction with Non-Subsidized Fuel at Pertamina SPBU in Pelalawan Regency–Riau Province. Journal of Ecohumanism, 3(3), 530–543.Ardhiansyah, N., Sri, M. S., & Yunanto, A. (2019). Impact of Brand Trust on Customer Satisfaction and Customer Loyalty. International Conference on Rural Development and Entrepreneurship 2019: Enhancing Small Business and Rural Development Towards Industrial Revolution 4.0, 2(9), 288–293.Azizan, N. S., & Yusr, M. M. (2019). The Influence of Customer Satisfaction, Brand Trust, and Brand Image Towards Customer Loyalty. International Journal of Entrepreneurship and Management Practices, 2(7), 93–108. https://doi.org/10.35631/ijemp.270010 Cuong, D. T., & Khoi, B. H. (2019). The relationship between service quality, satisfaction, trust, and customer loyalty was studied in a study of convenience stores in Vietnam. Journal of Advanced Research in Dynamical and Control Systems, 11(1 Special Issue), 327–333.Damayanti, C., & Wahyono. (2015). Pengaruh Kualitas Produk, Brand Image Terhadap Loyalitas Dengan Kepuasan Sebagai Variabel Intervening. Management Analysis Journal, 4(3), 236–251.Desiyanti, N. L., Sudja, I. N., & Budi Martini, L. K. (2018). Effect of Service Quality on Customer Satisfaction, Customer Delight and Customer Loyalty (Study on LPD Desa Adat Sembung and LPD Desa Adat Seseh). International Journal of Contemporary Research and Review, 9(03), 20660–20668. https://doi.org/10.15520/ijcrr/2018/9/03/483 Eliba, F., & Zulkarnain. (2017). Pengaruh Kualitas Pelayanan Dan Citra Perusahaan Terhadap Kepuasan Dan Loyalitas Nasabah Pada PT. Asuransi Jiwasraya (Persero) Di Kota Pekanbaru. Jurnal Tepak Manajemen Bisnis, 9(3), 88–104. Fajarianto, B., Lubis, N., & Saryadi, S. (2013). Pengaruh Kualitas Pelayanan Dan Brand Image Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan (Studi Kasus Pada Cv. Ahass Sahabat Sejati Motor Tembalang Semarang). Jurnal Ilmu Administrasi Bisnis S1 Undip, 2(2), 103079.Fanany, F., & Oetomo, H. W. (2015). Pengaruh Brand Image Dan Service Quality Terhadap Loyalitas Melalui Kepuasan Pelanggan. Jurnal Ilmu & Riset Manajemen, 4(1), 1–21.Fauzi, F., & Putra, P. (2020). Analisis Jalur Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Sebagai Variabel Intervening di Bank BNI Syariah. 11(1), 33–41.Fida, B. A., Ahmed, U., Al-Balushi, Y., & Singh, D. (2020). Impact of Service Quality on Customer Loyalty and Customer Satisfaction in Islamic Banks in the Sultanate of Oman. SAGE Open, 10(2). https://doi.org/10.1177/2158244020919517 Firmansyah, M. A. (2019). Pemasaran Produk dan Merek. Qiara Media.Hasan, A. (2013). Marketing. Media Pressindo.Indrasari, M. (2019). Pemasaran dan Kepuasan Pelanggan. Unitomo Press.Indratriyana, R., Utomo, A., & Nugroho, A. P. (2021). The Influence Of Trust Brand Image And Service Quality On Consumer Satisfaction In Pegadaian Cabang Sragen. AKTUAL : Jurnal Akuntansi Dan Keuangan, 6(1), 47–59.Irfandi, N., Halim, E. H., & Wijayanto, G. (2025). The Impact of Market Orientation, Product Innovation, and Competitive Advantage on the Marketing Performance of Culinary Enterprises: Empirical Study in Kampar Regency, Indonesia. Golden Ratio of Marketing and Applied Psychology of Business, 5(1), 79-94.Kotler, P. (2019). Manajemen Pemasaran. Erlangga.Kotler, P., & Amstrong, G. (2016). Manajemen Pemasaran. PT. Indeks Kelompok Gramedia.Kotler, P., & Keller, K. L. (2016a). Manajemen Pemasaran (Bob Sabran (ed.); Ed 13). Erlangga.Kotler, P., & Keller, K. L. (2016b). Marketing Management Global Edition (Vol. 15E). https://doi.org/10.1080/08911760903022556 Kuswandarini, K. I., & Annisa, A. A. (2021). Analisis pengaruh kualitas layanan, corporate image, dan customer relationship management terhadap loyalitas nasabah dengan kepuasan nasabah sebagai variabel intervening. Journal of Management and Digital Business, 1(1), 37–51. https://doi.org/10.53088/jmdb.v1i1.46 Lupiyoadi, & Hamdani. (2015). Manajemen Pemasaran Jasa. Edisi 2. Andi Offset.Minh, N. V., & Huu, N. H. (2016). The Relationship between Service Quality, Customer Satisfaction and Customer Loyalty : An Investigation in Vietnamese Retail Banking Sector. 8(2), 103–116. https://doi.org/10.7441/joc.2016.02.08 Novianti;, Endri;, & Darlius. (2018). Kepuasan pelanggan memediasi pengaruh kualitas pelayanan dan promosi terhadap loyalitas pelanggan. MIX: Jurnal Ilmiah Manajemen, Volume VIII, No. 1, Feb 2018, VIII(1), 90–108.Nurhidayat, A. I., & Maskur, A. (2022). Pengaruh kualitas layanan dan kepercayaan terhadap kepuasan serta dampaknya pada loyalitas nasabah: Studi kasus pada nasabah pt Pegadaian UPC Kuwu. YUME: Journal of Management, 5(2), 495–507. https://doi.org/10.37531/yume.vxix.343 Pakurár, M., Haddad, H., Nagy, J., Popp, J., & Oláh, J. (2019). The service quality dimensions that affect customer satisfaction in the Jordanian banking sector. Sustainability (Switzerland), 11(4), 1–24. https://doi.org/10.3390/su11041113 Pratama, H., & Suprapto, B. (2017). The Effect of Brand Image, Price, and Brand Awareness on Brand Loyalty: The Rule of Customer Satisfaction as a Mediating Variable. GATR Global Journal of Business Social Sciences Review, 5(2), 52–57. https://doi.org/10.35609/gjbssr.2017.5.2(9) Putri, L. T., Alwie, A. F., & Wijayanto, G. (2024). Marketing performance model and environment for micro business scale women-preneurs based on competence in the Province of Riau. Journal of Ecohumanism, 3(6), 2140-2149. Putri, L. T., Setiawan, A., Salis, M., & Ali, A. (2024). Membangun Loyalitas Pelanggan: Studi terhadap Kualitas Layanan, Harga, dan Kepuasan Di PT. J & T Ekspress Bangkinang. Jurnal Daya Saing, 10(2), 190-198.Rahmah, P., Rajeng, A. B., & Erpiana. (2020). Pengaruh Dimensi Kualitas Pelayanan Terhadap Loyalitas Nasabah PT. Pengadaian (Persero) Kantor Cabang Watansoppeng. Jurnal Ilmiah METANSI ”Manajemen Dan Akuntansi”, 3(2002), 46–52.Rangkuti, F. (2017). Customer Service Satisfaction & Call Center. PT. Gramedia Pustaka Utama.Sahid, A., Samsir, & Lestari, G. R. (2023). Pengaruh Kualitas Pelayanan dan Citra Perusahaan terhadap Kepuasan Konsumen dan Loyalitas Konsumen dimasa New Normal pada Lembaga TOEFL Indonesia di Pekanbaru. Daya Saing, 9, 370–379.Salis, M., Putri, L. T., & Putra, A. (2024). Pengaruh Varian Produk, Pelayanan Dan Fasilitas Terhadap Kepuasan Konsumen Pada Kafe Bolo di Bangkinang Kota. Journal of Sustainable Business Practices, 2(1).Subagja, I. K., & Susanto, P. H. (2019). Pengaruh Kualitas Pelayanan, Kepuasan Nasabah Dan Citra Perusahaan Terhadap Loyalitas Nasabah Pt. Bank Central Asia Tbk Kantor Cabang Pondok Gede Plaza. Jurnal Manajemen Bisnis Krisnadwipayana, 7(1), 69–84. https://doi.org/10.35137/jmbk.v7i1.249 Sugiyono. (2013). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung : Alfabeta.Sugiyono. (2018). Metode Penelitian Kuantitatif, Kualitatif dan R & D.Bandung:Alfabeta. Alfabeta.Suminto, A., & Maharani, S. (2020). Analisis Pengaruh Corporate Social Responsbility, Islamic Banking Service Quality dan Corporate Image terhadap Loyalitas Nasabah di Bank BRISyariah Kantor Cabang Pembantu Ponorogo. El-Barka: Journal of Islamic Economics and Business, 3(1), 51–79. https://doi.org/10.21154/elbarka.v3i1.2013 Supramono, G. (2016). Perbankan dan Masalah Kredit : Suatu Tinjauan di Bidang Yuridis. Rineka Cipta, 4(1).Tjiptono, F. (2015). Strategi Pemasaran Cetakan kelima. Andi Offset.Umboh, V. j;, & Mandey, Silvya, L. (n.d.). Analisis Kualitas Jasa Layanan Pengaruhnya Terhadap Kepuasan Nasabah Pada PT. Pegadaian (Persero) Cabang Teling. Jurnal EMBA, 2(3).Wemben, F. V, Mananeke, L., & Roring, F. (2020). Analisis Pengaruh Kualitas Pelayanan, Citra Perusahaan Dan Kepercayaan Terhadap Loyalitas Nasabah Pada Pegadaian Upc Tanjung Batu. Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis Dan Akuntansi, 8(4), 1119–1128.Wijaya, B. S. (2013). Dimensions of Brand Image: A Conceptual Review from the Perspective of Brand Communication. European Journal of Business and Management, 10(22), 107–114. https://doi.org/10.13140/ejbm.2013.55.65